Pengembangan Buku ASWAJA an-Nahdliyah di Perguruan Tinggi Sebagai Upaya Membentuk Sikap Moderat Bagi Mahasiswa di Universitas Nahdlatul Ulama Blitar - Kasanah, Siti uswatun (Universitas Nahdlatul Ulama Blitar, 2024)
The aim of this research is as a solution to ward off radical attitudes by instilling a Moderate attitude in students through the development of the Aswaja an-Nahdliyah reference book which is important to convey to students in tertiary institutions. This research uses a research design design to develop products, namely Research and Development (R&D) according to Thiagarajan, namely the 4-D model which consists of 4 research and development steps, namely defining, and designing , development, and dissemination. The solution to realizing a moderate attitude in students who are the nation's assets as the young generation is through cultivating the 5 social attitudes of Nahdlatul Ulama, namely Tawassut (being moderate), Tasamuh (being tolerant), Tawazun (being balanced) and I'tidal (being fair) and Amar ma'ruf Nahi Mungkar (inviting goodness and preventing evil) in understanding concepts, analyzing and will be realized in the implementation of attitudes that arise in real life in society, nation and state.